Influence of Integrated Nutrient Management on growth, yield and quality of tissue cultured banana (Musa × paradisiaca) cv Grand Naine - NAYYER, MD ABU; TRIPATHI, V K; KUMAR, SANJEEV; LAL, DEEPA; TIWARI, BHARAT (The Indian Journal of Agricultural Sciences, 2014)
To examine the influence of integrated nutrient management on growth, yield and quality of tissue cultured banana (Musa × paradisiaca L.) cv Grand Naine, a study was conducted during 2010-11 in the Department of Horticulture, C S Azad University of Agriculture and Technology, Kanpur (UP), India. The experiment was laid out in randomized block design with three replications and ten treatments. It was recorded that the height of pseudostem (150.27 cm), girth of pseudostem (67.98 cm), total number of leaves (34.66), total number of functional leaves at the time of emergence of inflorescence (17.33), length of inflorescence (118.50 cm) were maximum in the plants supplied with 100% RDF of NPK+50 g Azospirillum+50 g PSB+50g Trichoderma harzianum per plant with earliness in flowering (253.33 days) and flowering to harvesting of bunch (110.00 days) as compared to others. Same treatment also resulted maximum bunch weight (24.50 kg), number of fingers per hand (19.33) and per bunch (160.00), number of hands per bunch (8.33), finger weight (140.00 g), length (20.33 cm), diameter (15.20 cm), TSS (19.26 0Brix), total sugars (18.66%), pulp percentage (82.17%) and pulp:peel ratio (4.60) with reduced peel percentage (17.83%) and titratable acidity (0.40%).